Rotaxanes with dynamic mechanical chirality: Systematic studies on synthesis, enantiomer separation, racemization, and chiral-prochiral interconversion - Ishiwari, Fumitaka; Takata, Toshikazu (Frontiers in Chemistry, 2022)
Dynamic mechanical chirality of [2]rotaxane consisting of a Cs symmetric wheel and a C2v symmetric axle is discussed via the synthesis, enantiomer separation, racemization, and chiral-prochiral interconversion. This [2]rotaxane is achiral and/or prochiral when its wheel locates at the center of the axle, but becomes chiral when the wheel moves from the center of the axle. These were proved by the experiments on the enantiomer separation and racemization. The racemization energy of the isolated single enantiomers was controlled by the bulkiness of the central substituents on the axle. Furthermore, the chiral-prochiral interconversion was achieved by relative positional control of the components. The present systematic studies will provide new insight into mechanically chiral interlocked compounds as well as the utility as dynamic chiral sources.